ANALISIS KELAYAKAN PELAKU USAHA MIKRO KECIL MENENGAH PADA PEMBUATAN MINYAK TRADISIONAL SAAT PANDEMI COVID-19 DI KOTA DENPASAR - admin, jekt; Dewi, Made Diah Purnama; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 3 (2024): Vol.13.No.3.MARET 2024 [161-247], 2024)
Micro, Small and Medium Enterprises (MSMEs) in Denpasar  are important assets in strengthening the foundation of the regional economy. The MSME sector is currently at the heart of the government's concern, which is trying to recover immediately  from the downturn caused by the Covid-19 pandemic that has affected all sectors of the economy, like like the traditional MSME oil sector. This phenomenon explains that MSMEs are efficient enterprises developed to support the macroeconomic and microeconomic development of Indonesia as well as the sectors that inspire other countries to develop.Rephrase Therefore, special attention should be paid to the epidemic situation for MSMEs. For some economic actors, the pandemic situation is an opportunity to plan for business development after Covid-19, which is why it is necessary to study the feasibility. This study  was carried out in Denpasar city with a total sample of 4 MSMEs with the method of business feasibility analysis, i.e. testing whether  the business is viable or not. Research results  show that: Using the business feasibility analysis method, the business is feasible  in the city of Denpasar.   keyword : MSME, business feasibility, covid-19 pandemic